Pengaruh Larutan Kumur Probiotik Terhadap Peningkatan pH Saliva - Ratnasari, Destya Mega; , drg. Mahmud Kholifa, MDSc; , drg. SE Yuletnawati, MDSc (2015)
Oral cavity disorder which have high prevalence in the community is dental caries. Dental caries occur because carbohydrate fermentation by Streptococcus mutans to form acidic condition in the oral cavity which also affect salivary pH be acidic. Acidic salivary pH cause saliva not able maintain tooth enamel. One of one of the ways that can be done to remain normal salivary pH is using probiotic gargle solution. Probiotic gargle solution quite safety to use without any side effects because adding the normal bacteria of oral cavity that can reduce Streptococcus mutans which major cause of dental caries. The purpose of this study was to determine the effect of probiotic gargle solution to salivary pH and to determine probiotic gargle solution can increase salivary pH. This study was quasi experimental with study design of one group pretestposttest. Subjects were 32 children of Ad-Dhuhaa Orphanage Foundation Surakarta. Subject was measured salivary pH before and after gargled using 10 ml probiotic gargle solution for 60 seconds. Five minutes after gargled, respondents were instructed to spit for 1 ml then salivary pH measured using digital pH meter 0.0-14.0 with sensitivity 0.01 from senseLine F410. Salivary pH measurement results were analyzed statistically by Paried T-Test method. The results showed that P value = 0.000 (<0.05), which mean that there was significant difference between before and after gargled using probiotic gargle solution. So it could be concluded that probiotic gargle solution could effectively increase the salivary pH.